STRATEGI PENGEMBANGAN WISATA UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN PADA OBJEK WISATA HUTAN PINUS TO’NAKKA’ ULUSALU KABUPATEN TANA TORAJA - Hilda Arruan Saratu’; Mey E. Limbongan; Helba Rundupadang (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to identify tourism development strategies to increase tourist visits to the To’Nakka Ulusalu Pine Forest tourist attraction in Tana Toraja. The data collection procedures for this research include observation, interviews, and documentation. The method used in this study is a qualitative approach with SWOT analysis.The results indicate that the To’Nakka Pine Forest tourist attraction has great potential to be developed into an appealing tourist destination while promoting the region’s natural tourism potential. The conclusion of this study emphasizes that with proper management, the To’Nakka Pine Forest can become a tourism destination that supports the local economy and introduces Tana Toraja to the international tourism stage. Keywords: Development Strategy, Increasing Visits, Boosting Local Economy.